(untitled) (Research, Society and Development, 2020)
The objective was to fractionate carbohydrates and subjected feed proteins or no irrigation. Were evaluated: Panicum maximum, Urochloa brizantha, Andropogon gayanus, Urochloa humidicola and Digitaria Umfolozi, subject to two levels of irrigation. The experimental design was a 5x2 factorial arrangement with four replications. The forages were planted in plots with 4 m², two cuts were performed with an interval of 45 days. The forages were evaluated for crude protein (CP) and digestible crude protein (DCP), neutral detergent fiber (NDF), hemicellulose, acid detergent fiber (ADF), cellulose and lignin. Fractionation of CP and CHO was done according to the CNCPS. There was a significant interaction for CP and DCP (P<0.05). The P. maximum showed higher levels of CP and DCP in two levels of irrigation, the CP and DCP content reduced in irrigated fodder. Irrigation reduces the content of the most digestible fractions (A, B1 and B2) of CP and increased content of less digestible (B3 and C). The cell wall components (NDF, hemicellulose, ADF, cellulose and lignin) were not affected by irrigation (P>0.05). The U. brizantha presented the highest content of cell wall components and fractions of CT. It was observed that the irrigation increased the percentage of CT fodder, no effect of irrigation (P>0.05) in fractions of CT.